Strategi Diplomasi Pengetahuan German Academic Exhange Service (DAAD) Dalam Mendukung Kerjasama Internasional Bidang Pendidikan Tinggi di Indonesia - Muhammad Faisal Aziz; Amalia, Rizki Septin (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2025)
This article analyzes the strategies of the German Academic Exchange Service (DAAD) in supporting international collaboration in higher education, particularly in Indonesia. The issue examined is the role of DAAD as an instrument of public diplomacy and knowledge within the framework of German foreign policy. This research employs a qualitative descriptive method through a literature review of official DAAD sources and academic literature. The DAAD not only reinforces Germany's image as a knowledge-based nation but also builds strategic bilateral relationships through academic exchange programs. Thus, it can be concluded that the knowledge diplomacy carried out through the DAAD is an effective approach in expanding Germany's influence collaboratively on the global stage. Keywords: International Relations, DAAD, Soft Power, Knowledge Diplomacy